Local de produção, armazenamento e qualidade de sementes de soja - Sanches, Maurício Feis Ganz [UNESP] (2015)
The soybean is produced across the country, however, environmental and phytosanitary factors may limit the obtaining of seed of physiological and sanitary quality satisfactory. Thus, the present study aimed to evaluate the physiological, sanitary and chemical quality, initial and during the storage of soybean seeds cultivars harvested at production sites with different soil and climatic characteristics and verify the influence of genotype-environment relationship. It was used seeds of two soybean cultivars early cycle (M-SOY 7908 RR and CD 2630 RR) from four regions with different edaphoclimatic characteristics. Seeds were evaluated by germination, vigor (accelerated aging, electrical conductivity and tetrazolium), sodium hypochlorite, sanity, determination of oil content and seedling emergence in the field tests. After determining the initial seed quality, seeds were stored in a dry chamber (20 ± 2 °C and 45% RH of air) and evaluated again after six and 12 months. It was observed to MSOY 7908 RR cultivar that the region of Perdizes (altitude 1,030 m) was favorable for production of seeds with high physiological, chemical and sanitary quality when compared to those from Casa Branca (altitude 600 m), due to milder weather conditions verified in the first city. Regarding the CD 2630 RR cultivar, seeds produced in Altinópolis (altitude 980 m) had lower physiological, chemical and sanitary quality when compared to those from Sales Oliveira (region with lower altitude), differing from results found in the literature. This behavior was due to the high precipitation and temperature verified during the pre-harvest, causing moisture damage harmful to performance. In both cultivars and four production sites studied, there was reduction of the physiological and chemical quality during storage. Furthermore, the pathogens initially present in the seeds also showed decline as its incidence. Thus, seeds with high physiological, chemical and ...